Psychometric Validation of the CLEFT-Q Patient Reported Outcome Measure: A Prospective Study to Examine Cross-Sectional Construct Validity. (March 2023) - Miroshnychenko, Anna; Rae, Charlene; Riff, Karen Wong; Forrest, Christopher; Goodacre, Tim; Swan, Marc; Slator, Rona; Goldstein, Jesse; Thoma, Achilleas; Harman, Karen; Klassen, Anne
Objective: CLEFT-Q is a condition-specific patient-reported outcome measure (PROM) for patients with cleft lip and/or palate (CL/P). The aim of this study was to examine the cross-sectional construct validity of the CLEFT-Q scales. Design: Construct validity was assessed through a prospective study that tested hypotheses regarding correlations of scores with other PROMs that measure related constructs. Setting: Seven cleft centres in Canada, the USA, and UK were involved. Patients/Participants: Patients were aged eight to 29 years with CL/P. Interventions: Before undergoing rhinoplasty, orthognathic, cleft lip scar revision, and alveolar bone graft, participants were asked to complete the following PROMs: CLEFT-Q (9 scales), Child Oral Health Impact Profile (socio-emotional subscale) and Cleft Hearing Appearance and Speech Questionnaire (features 1 subscale). Main Outcome Measure(s): The correlation coefficients examining the relationship between the scales were the main outcome measures. Correlations (Spearman) were calculated and interpreted as follows: <0.3 weak, 0.30 to 0.50 moderate, ≥0.50 strong. Results: Participants ( n = 177) were mostly male (61%) and aged between eight and 11 years (42%). Overall, 38 of 52 (73%) hypotheses tested were supported. More specifically, 20 of 26 (77%) hypotheses about correlations between the appearance scales were supported, two of three (67%) hypotheses about correlations between the health-related quality of life scales were supported, and 16 of 23 (70%) hypotheses about correlations between the appearance and health-related quality of life scales were supported. Conclusions: Cross-sectional construct validity of the CLEFT-Q scales adds further evidence of the psychometric properties of this instrument.